The Using Of Instagram Caption To Improve Students Writing Ability For The Tenth Grade Students Of SMA Swasta Yayasan Perguruan Keluarga Kota Pematang Siantar - Benarita Purba; Rohdearni Wati Sipayung; Dita Sintia (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The objective of the study is to know whether using instagram caption can improve students writing ability in SMA Swasta Yayasan Perguruan Keluarga Pematang Siantar. This research used quantitative with true experimental method approach. Population of this research was tenth grade with 6 classes which consists of 200 students and the sample of this research was 30 students in one classes. The technique of collecting data was pre-test and post-test. The technique of analyzing data by using SPSS version 26.0. The result of research was Tcount(15,310) > Ttable(1,699) at the significance level α = 0,05 with the degrees of freedom (df) = (30-1=29) for each class so the degrees of freedom is 29. It means that Ho is rejected and Ha is accepted. The Instagram caption can help improve students' writing skills because the results of data analysis show that there are significant . The Instagram application using the caption can be used as a media in improving students' writing skills. After being implemented in tenth grade of SMA Swasta Yayasan Perguruan Keluarga Pematang Siantar.